Chien, chèvre, taureau, couvée, ou le personnage de théâtre à l’épreuve du bestiaire johnstonien - Virginie Girel-Pietka (Sillages Critiques)
According to Hamlet, drama aims to “hold […] the mirror up to nature”. Yet such a task has become quite a challenge since the 20th century, as history keeps unsettling the very notion of human nature. Denis Johnston’s attempt to explore that nature on the stage therefore led him to unsettle that poetics which did not make any sense any more. In Táin Bo Cuailgne (1956) and in The Golden Cuckoo (1979), a dog, a bird-witch, a bull, a goat and a rooster challenge the notion of human nature as well as that of a character. They interfere with the protagonists’ fates, either physically or metaphorically, and lead them to rebel against the society they live in. I argue that becoming outstanding theatrical performers allows them to make sense of their respective stories and therefore to redefine human nature by reconfiguring the poetics of theatre.